Analisis Dampak Impor, Inflasi, dan Suku Bunga Terhadap Pertumbuhan Ekonomi Periode Tahun 2018-2022 - Mentari, Resa Mentari (Jurnal Ekonomika : INDEPENDEN, 2023)
ABSTRACT This research studies to determine the effect of inflation and interest rates on Indonesia's economic growth for the 2018-2022 period. The data used in this study are secondary data, namely inflation and deviating interest rates from the websites of Bank Indonesia and the Central Bureau of Statistics (BPS). The method used is multiple linear regression. Regression research results show that simultaneously inflation and interest rates have a significant effect on Indonesia's economic growth in 2018-2022.